Geometric microliths as chronological and cultural markers in the Sado shell middens? Reflections from Amoreiras (Alcácer do Sal, Portugal) - Nukushina, Diana (2015)
The production of geometric microliths from bladelets has been identified as one of the main strategies of lithic production during the Late Mesolithic in southwestern Portugal. The Sado shell middens generally possess an abundance of these tools, similarly to sites found in other regions. However, systematic lithic studies are still scarce. In this work, we discuss the value of the geometric microliths as chronological and cultural markers, through the analysis of lithic remains from Amoreiras shell midden (Alcácer do Sal). First, a formal characterization of this assemblage is performed. Second, a diachronic and cultural perspective of these materials in the Sado shell middens is provided. Finally, a comparison with other Late Mesolithic and the Early Neolithic assemblages from southwestern Iberia is presented. A set of lithic remains from Amoreiras, which was recovered in the 1950s and 1960s, was subject to a techno-typological analysis, following the assumptions of the ‘chaîne opératoire’. Also, a statistical analysis, including variance analysis, was performed. This work shows that the geometric microliths from Amoreiras clearly represent one of the main purposes for the debitage at this site, which presents an outstanding typological and size uniformity. The characteristics found by this study suggest the existence of a well-standardized production of geometric microliths. This production scheme would be more economic in terms of raw material requirements and production time-effort. The material and chronometrical data from Amoreiras contradicts the cultural uniformity perspective for this specific site and for the Sado shell middens in general. Moreover, in light of the presented data, a strict chrono-cultural significance of the segment dominance is difficult to sustain. Despite the standardized production and the importance given to geometric microliths, the data provided by the forms and their variations is still insufficient for a comprehensive approach to the social issues in the Sado valley, during the Mesolithic-Neolithic transition.